2014
DOI: 10.2147/ijn.s56582
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic transmission electron microscopy of recombinant tuberculosis vaccine antigen with anionic liposomes reveals formation of flattened liposomes

Abstract: Development of lipid-based adjuvant formulations to enhance the immunogenicity of recombinant vaccine antigens is a focus of modern vaccine research. Characterizing interactions between vaccine antigens and formulation excipients is important for establishing compatibility between the different components and optimizing vaccine stability and potency. Cryogenic transmission electron microscopy (TEM) is a highly informative analytical technique that may elucidate various aspects of protein- and lipid-based struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…18 ). The thickness of these liposomal membranes was estimated at about 5 nm, which was in accordance with the bilayer thickness of liposomes reported in the previously worked liposomes 31 , 32 . Next, we investigated the pH-responsive cleavage of DA groups from ICG/L-G2R-DA by measuring the pH-dependent change of zeta potential of samples.…”
Section: Resultssupporting
confidence: 91%
“…18 ). The thickness of these liposomal membranes was estimated at about 5 nm, which was in accordance with the bilayer thickness of liposomes reported in the previously worked liposomes 31 , 32 . Next, we investigated the pH-responsive cleavage of DA groups from ICG/L-G2R-DA by measuring the pH-dependent change of zeta potential of samples.…”
Section: Resultssupporting
confidence: 91%
“…The results detected by DLS and fl-NTA showed that the addition of P188 did not change the size distribution of liposomes ( Table S6 and 7 ). TEM results showed that after P188 was added to liposomes and incubated for 2 h (37°C), discontinuous segments appeared on the lipid bilayer, indicating the heterogeneity of the liposomal membrane 50 ( Figure 6C ). FRET technology was employed to investigate the structural stability of liposomes.…”
Section: Resultsmentioning
confidence: 99%
“…The NLs suspension (4 µl) was put on a clean grid, blotted away the excess (if any) with the help of filter paper and vitrified instantly by dipping into liquid ethane. The grid was stored in liquid nitrogen till shifting under the electron microscope (Tecnai Polora, version 4.6 FEI Tecnai G2, Eindhoven, Netherlands) which was operated at 300 kV equipped with an FEI Eagle 4 K × 4 K charge-coupled device (CCD) camera for capturing the images (Fox et al., 2014 ).…”
Section: Methodsmentioning
confidence: 99%